'A magical balance of opposites': Reading Luigi Ghirri's photography through Walter Benjamin. Issue 2 (1st June 2014) - Spunta, Marina
In this article I contend that Ghirri's photography can fruitfully be read through Benjamin' thought, in particular through his key notions of experience, montage, aura, beauty, mystery and dialectical image, and at the same time I seek to redress a common misreading of Benjamin's work in some art theory. This approach allows me to illuminate from a new angle Ghirri's aesthetics and the change it underwent between the late 1970s and the early 1980s, and to demonstrate that his work effectively draws on Benjaminian dialectics to achieve a 'magical balance of opposites'. Through a close analysis of selected Ghirri's photographs from two of his main series from the 1970 – Kodachrome (1970–1978) and Still life (1975–1979) – and from two series from the 1980s – Il profilo delle nuvole/The Outline of Clouds (1980–1989) and Atelier Morandi (1989–1990) – I show that Ghirri's photography moves from an early effort to deconstruct the assemblage of images that compose reality to an attempt to re-create an aura of places that are felt to be on the brink of disappearing. In so doing he both expressed a postmodern sense of loss of experience and history and challenged this by presenting photography as a means of achieving knowledge and experience of the world, before the onset of the digital age.